(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Nosocomial infection is the most common undesirable phenomenon in healthcare that affects patient safety. They contribute to significant morbidity, mortality and financial burden for patients, families and health systems. The burden of hospital-acquired infection worldwide is unknown due to the lack of surveillance systems for hospital-acquired infection. Nevertheless, infection prevention and control programs have made great efforts to develop surveillance systems and infection control methods. Known pathogens include methicillin-resistant staphylococcus aureus, vancomycin-intermediate staphylococcus aureus and vancomycin-resistant Staphylococcus aureus, Enterobacteriaceae with resistance to extended-spectrum cephalosporins compatible with extended-spectrum beta-lactamases.production of vancomycin-resistant Enterococcus, carbapenem-resistant Enterobacteriaceae and Acinetobacter species, as well as drug-resistant Pseudomonas aeruginosa. Immunocompromised patients and people with permanent devices such as central catheters or urinary catheters are usually associated with opportunistic infections with fungal pathogens. Nosocomial infections are caused by Candida fungi, including species such as C. albicans, C. parapsilosis and C. glabrata. As an emerging organism worldwide, Candida auris is a serious problem. This is due to multidrug resistance and high morbidity and mortality due to difficulties with diagnosis and a high rate of unsuccessful treatment. The unsafe practice of using needles may involve hepatitis B and C acquired in medical institutions and the human deficiency virus (HIV).Nosocomial infections have a wide range of complications, which depend on the type of infection, the severity of the disease and the suspected pathogen. The complications caused by each type of hospital-acquired infection can be very different, but some of the most common are listed below. Thus, it is expected that the introduction of published and evidence-based infection control protocols will significantly reduce the likelihood of pathogen transmission and the overall incidence of nosocomial infections.